Awareness and experiences of cosmetic treatment providers with body dysmorphic disorder in Saudi Arabia - Kattan, Abdullah E.; Alnujaim, Nujaim H.; Barasain, Omar; Bouman, Theo K.; AlHammad, Reema; Van der Lei, Berend (PeerJ (San Francisco, CA), 2020)
Body Dysmorphic Disorder (BDD) is defined as a constant obsession with one’s external appearance and flaws, and it falls under the criteria of neuropsychiatric disorders. Individuals suffering from this disorder may seek unnecessary cosmetic procedures from cosmetic treatment providers such as dermatologists or plastic surgeons. Cosmetic treatments have become readily available, which has led to an influx of undiagnosed BDD patients electing to undergo such treatments. Therefore, physicians should have the clinical knowledge about BDD to diagnose and manage these cases to avoid psychological and physical harm to these patients. However, there were no studies conducted in our region to assess the awareness of BDD among physicians who provide cosmetic treatments with regards to their attitude toward such cases and how they would manage it. This study aims to assess the awareness of Body Dysmorphic Disorder among Saudi physicians who provide cosmetic treatments. We conducted an observational cross-sectional study among physicians practicing in hospitals and cosmetic clinics in Riyadh and Jeddah city (Saudi Arabia), who perform cosmetic procedures, namely dermatologists, plastic surgeons, and otorhinolaryngologists. A paper-based questionnaire consisting of multiple-choice questions was distributed among them. The total number of participants was 155 physicians: 113 (72.9%) males and 42 (27.1%) females. Eighty-two (52.9%) participants reported that they have been familiar with the diagnostic criteria of BDD for a long time and ninety-nine (63.8%) reported being familiar with the clinical picture of BDD. Sixty-three (40.6%) participants estimated the prevalence of BDD cases seen in cosmetic practice to range from 1%-5%, and most agreed on an equal prevalence of BDD among female and male patients. Half of the participants ( n = 76) (49%) reported that they sometimes share knowledge about BDD with patients whom they suspect to suffer from this condition. In conclusion, cosmetic treatment providers in Saudi Arabia are aware of BDD, but we have identified a discrepancy between the self-reported participant knowledge of diagnostic criteria and their ability to accurately estimate the prevalence of BDD cases seen in clinical practice.